Educational leadership competencies and Malaysia education development plan 2013-2025 - Don, Yahya; Raman, Arumugam; Daud, Yaakob; Kasim, Kamarudin; Omar Fauzee, Mohd Sofian (UniversityPublications.net, 2015)
This study is aimed at identifying the influences of emotional competence on leadership practices among mid-level leaders in secondary schools in Kedah, for the formation and development of schools’ leadership succession planning.This is a quantitative approach in cross-sectional survey to collect data on the current situation pertaining to emotional competence and Distributive leadership practices among school leaders.The population of this study involved mid-level leaders in secondary schools in Kedah. The stratified random sampling was used to select samples for the research population.The instruments used in this research were Emotional Competency Inventory (ECI - 2) (Boyatiz, 2001) and Leadership Practices Inventory (LPI) (Kouzes & Posner, 1995).This study found that there was a significant and positive relationship between emotional competence and Distributive leadership. The multiple regression analysis showed a significant and positive relationship between subscales of emotional competence and Distributive leadership practices.In view of that, the elements of self- awareness, social awareness, self management and relationship management groups should be considered as important elements in the planning of programs aimed at upgrading the level of leadership skills while reinforcing the qualities of school leaders in national secondary schools which will directly contribute to raising the level of educational excellence as per the plans and objectives of the Malaysian Education Blueprint (2013 – 2025).